2016
DOI: 10.1002/2016gc006316
|View full text |Cite
|
Sign up to set email alerts
|

Overriding plate, mantle wedge, slab, and subslab contributions to seismic anisotropy beneath the northern Central Andean Plateau

Abstract: The Central Andean Plateau, the second‐highest plateau on Earth, overlies the subduction of the Nazca Plate beneath the central portion of South America. The origin of the high topography remains poorly understood, and this puzzle is intimately tied to unanswered questions about processes in the upper mantle, including possible removal of the overriding plate lithosphere and interaction with the flow field that results from the driving forces associated with subduction. Observations of seismic anisotropy can p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 65 publications
7
14
0
Order By: Relevance
“…The ambient conditions in the mantle wedge beneath the active volcanic arc with elevated temperatures and high water content are favorable for the occurrence of C‐type olivine [ Karato et al , ], which would be the best candidate to explain the observed pattern. This scenario would be consistent with trench‐parallel flow in the back‐arc mantle wedge further to the south recently inferred from the local splitting [ Long et al , ].…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…The ambient conditions in the mantle wedge beneath the active volcanic arc with elevated temperatures and high water content are favorable for the occurrence of C‐type olivine [ Karato et al , ], which would be the best candidate to explain the observed pattern. This scenario would be consistent with trench‐parallel flow in the back‐arc mantle wedge further to the south recently inferred from the local splitting [ Long et al , ].…”
Section: Discussionsupporting
confidence: 89%
“…The model for upper mantle anisotropy obtained in this study provides constraints complementary to those provided by shear wave splitting, which has previously been studied in this region by Eakin et al [, , ] and Long et al []. Here we briefly discuss the comparison between the two types of studies, illustrated in Figure .…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations